Smart Plant Monitoring Sistem Suhu dan Kelembaban Tanah Pada Tanaman Cabai Berbasis IoT Menggunakan Protokol MQTT - Dini Berlian; Linna Oktaviana Sari (LPPM Universitas Potensi Utama, 2026)
Chili plants are very sensitive to environmental conditions, especially soil temperature and humidity, so they require continuous monitoring. Manual monitoring methods for chili plants are considered ineffective because they do not allow for continuous monitoring of changes in environmental conditions and do not always provide accurate and real-time information. In addition, the network infrastructure at the research site is still unstable due to limited Wi-Fi coverage and poor internet signal quality in relatively remote cultivation areas. Therefore, this study uses the Message Queue Telemetry Transport (MQTT) protocol, which is lightweight and efficient for data communication in limited network conditions. This study aims to design an IoT-based soil temperature and humidity monitoring system using the MQTT protocol. The method used is an experiment with a prototype approach. Sensor data is sent in real-time and displayed on an LCD and Node-RED dashboard that can be accessed via a laptop and smartphone. Testing was conducted for five days at three different times, namely morning, afternoon, and night. The results show that the system is capable of real-time monitoring and consistently displays soil temperature and humidity data according to the actual conditions of chili plants. Therefore, the IoT-based monitoring system using the MQTT protocol can be used to support real-time monitoring of chili plant conditions.